PENGARUH PERBANDINGAN SARI TAPE BERAS KETAN HITAM DENGAN SARI TAPE JAGUNG DAN PENAMBAHAN DESKTRIN PADA PEMBUATAN BREM PADAT (The Effect of Black Sticky Rice Extract Tape and Corn Extract Tape rasio and Dextrin Addition for solid Brem Production) - Jurnalis Jurnalis; Herla Rusmarilin; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2019)
The aim of this research was to determine the effect of black sticky rice extract tape and corn extract tape ratio and the addition of dextrin for solid brem production. This research was conducted using completely randomized design with 2 factors i.- e,ratio of black sticky rice extract tape and corn extract tape (J) (80%:20% ; 70%:30% ; 60%:40%: ; 50%:50%) and dextrin addition (D) (10%, 15%, 20%, 25%).The parameters analyzed were moisture content, ash content, alcohol content, pH, total acid, total soluble solid, organoleptic hedonic value of color, flavor, taste, and texture. The results showed that the ratio of black sticky rice extract tape and corn extract tape had highly significant effect on moisture content, alcohol content, pH, total acid, total soluble solid, and hedonic test of taste of the solid brem. Moreover, the tratmen had a significant effect on ash content. The addition of dextrin had a highly significant effect on moisture content, alcohol content, total acid, total soluble solid, and organoleptic hedonic value of taste and it had a significant effect on ash content. Interaction between the two factors had a highly significant effect on total acid, total soluble solid, and organoleptic hedonic value of taste. The best quality of brem solid production was formulated by the mixture of black sticky rice extract tape and corn extract tape (50%:50%) with the addition of 25% dextrin Keywords : black sticky rice tape, corn tape, dextrin, solid brem ABSTRAK Penelitian ini dilakukan untuk mengetahui Pengaruh perbandingan sari tape ketab hitam dengan sari tape jagung dan penambahan dekstrin pada pembuatan brem padat. Penelitian ini menggunakan rancangan acak lengkap dengan faktorial 2 faktor, yaitu perbandingan sari tape ketan hitam dengan sari tape jagung(J) (80%:20% ;70%:30% ; 60%:40%: ; 50%:50%) dan jumlah penambahan dekstrin (D) (10%, 15%, 20%, 25%). Parameter yang dianalisa adalah kadar air, kadar abu, kadar alkohol, nilai keasaman, total asam, total soluble solid, nilai organoleptik warna, aroma, rasa, dan tekstur. Hasil penelitian menunjukkan bahwa perbandingan sari tape ketan hitam dengan sari tape memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar alkohol,nilai keasaman, total soluble solid , dan uji organoleptik rasa, memberikan pengaruh berbeda nyata terhadap kadar abu. Penambahan dekstrin memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar alkohol, total asam, total soluble solid , uji organoleptik hedonik rasa, memberikan pengaruh berbeda nyata  terhadap kadar abu. Interaksi kedua faktor memberikan pengaruh berbeda nyata terhadap total asam, total soluble solid, dan nilai hedonik rasa. Perbandingan sari tape ketan hitam dengan sari tape jagung (50%:50%) dan penambahan dekstrin 25% memberikan pengaruh yang terbaik untuk mutu brem padat.   Kata Kunci :tape ketan hitam, tape jagung, dekstrin, brem padat